Ultrasonography in Early Diagnosing Birth-associated Distal Femoral Physeal Fractures: A Case Series and a Reminder to Perinatologists - Pao-Sheng Peng; Kai-Yuan Cheng; Shih-Chia Liu (Formosan Journal of Musculoskeletal Disorders)
Birth-related traumatic epiphyseal fracture is uncommon. We reported three cases of distal femoral epiphysis fracture in the process of delivery. This type of injury could be difficult to detect in the newborn by plain radiographs because of the nonossification of the epiphysis. Therefore, the use of sonography is helpful to make an early and accurate diagnosis and unnecessary examination and blood laboratory tests can be avoided. Through these three cases in a row, we will see the diagnostic value of high-resolution ultrasonography in diagnosing newborn injuries of the limbs, and particularly in the diagnosis of radiographically occult epiphyseal fracture. Practitioners around the perinatology should bear this rare injury in mind.